Characteristics properties of soft soil treated with termite mound clay - Noorkhairunisa Materang (School of Environmental Engineering, University Malaysia Perlis, 2016)
The aim of this research is to investigate the improvement of the soft soil when treated with termite mound clay. Knowing the characteristics of soils is very important in preliminary stage of construction project. The conditions of local soil often cause difficulties to the construction project in Malaysia. The characteristics of soft soil such as Perlis marine clay which is normally with high water content and low shear strength thus forms a great challenge to geotechnical engineers. In this study chemical treatment is chosen as a solution to enhance engineering properties of soft soils. Chemical treatment that has been used is termite mound clay. The test was conducted on two different sample of termite mound clay that indicates by TMC I and TMC II. Overall objectives of this study are to investigate the improvement of soft soil treated with termite mound clay. The quantities of 5 %, 10 %, 15 %, 20 %, 25 % and 30 % of termite mound clay were added to the marine clay by weight. Then, Particle size distribution and Atterberg limit test conducted to determine the classification of soil and unconfined compression test conducted to identify shear strength of the soil. Based on physical analysis, the result for marine clay getting from Atterberg limit shows that the marine clay is high plasticity silt. From this research, sample TMC I shows stable improvement when added to the marine clay.